Economic Development Strategy of Halal Tourism in Sembalun Lombok Timur - Lestari, Riri (Sumatra Journal of Disaster, Geography and Geography Education, 2017)
Abstract The purpose of this research is to create Economic Development Strategy in Halal Tourism Area in Sembalun of East Lombok Regency and formulate economic development strategy by doing analysis of AHP (Analythical Hierarchy Process). How to take informants in this study using Purposive Sampling. Based on the results of the analysis and discussion that has been done before, the strategy of Economic Development of Halal Tourism Area In Sembalun, East Lombok Regency is still in the low category seen from the income of society and life is still very simple. To overcome these problems then need some strategies that are growth strategy, development strategy and equity, and strategy with insight of space. The criteria for economic development are 1) capital assistance for society (0.863) 2) IT based technology (0.819) 3) Increasing employment opportunities for the community (0.781) 4) Higher education 0.716 5) Reducing Unemployment (0.673).